2017
DOI: 10.1111/pai.12704
|View full text |Cite
|
Sign up to set email alerts
|

Indoor fungal diversity in primary schools may differently influence allergic sensitization and asthma in children

Abstract: Although no causal relationships could be established, exposure to higher fungal diversity was protective against allergic sensitization but this was not seen for asthma. In contrast, higher exposure to Gram-negative endotoxins and Penicillium spp in primary school's classrooms was associated with increasing odds of allergic sensitization in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The present study was conducted using the ARIA study database . Briefly, a total of 20 public primary schools located in the city of Porto, Portugal, were invited to participate in this cross‐sectional survey, corresponding to a total of 71 assessed classrooms.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was conducted using the ARIA study database . Briefly, a total of 20 public primary schools located in the city of Porto, Portugal, were invited to participate in this cross‐sectional survey, corresponding to a total of 71 assessed classrooms.…”
Section: Methodsmentioning
confidence: 99%
“…51 In a recent study, Rufo et al showed that classrooms with increased fungal diversity scores showed a significantly lower prevalence of children with atopic sensitization, but not asthma. 52 More studies are needed to evaluate the role of fungal diversity on the development of allergic diseases.…”
Section: The School Environmentmentioning
confidence: 99%
“…According to the “biodiversity hypothesis,” a lower exposure to the natural environment and biodiversity may adversely affect the human microbiome and its immunomodulatory capacity 2 . This hypothesis has been demonstrated in studies either showing lower microbiota diversity in the airways of children with asthma or finding a lower prevalence of atopic disease in children living the first years of their lives surrounded by a diverse microbiological environment 2‐6 …”
Section: Introductionmentioning
confidence: 99%